Equine uterine sanitizer: in vitro inhibition of endometritis-causing microorganisms and its stability to dilute antibiotics - Mazzuchini, Mariana P. [UNESP]; Lisboa, Fernando P. [UNESP]; Segabinazzi, Lorenzo G.; Canisso, Igor F. (Elsevier, 2024)
Endometritis is the leading cause of mare subfertility. Most mares respond to standard therapy, but alternative therapies have been developed for mares failing to respond. This study aimed to investigate a commercially available, yet unassessed, product labeled as a uterine sanitizer to determine the in vitro antimicrobial activity against microorganisms associated with endometritis and its in vitro stability to dilute antibiotics. In experiment 1, the microdilution broth technique and antimicrobial effects were assessed against Escherichia sp, Staphylococcus sp., Klebsiella sp., Pseudomonas sp., and Candida sp. Percentage inhibition was calculated by comparing the optical density. The minimum inhibitory concentration (MIC) 100% was determined using the resazurin dye technique. MIC 50% and 90% were determined using a dose-response non-linear regression. In experiment 2, the uterine sanitizer was used to dilute commonly used antibiotics achieving a final volume of 90 mL at 5°C, 21°C, and 37°C. The pH was measured at 0, 1, 3, 6, and 24 h after dilution. The uterine sanitizer had inhibitory properties against all microorganisms; Escherichia sp. being the most susceptible, and Pseudomonas sp. the most resistant. The uterine sanitizer had an acidic pH=4; however, when combined with the antibiotics, the pH of the antibiotic remained unchanged with the different temperatures and did not precipitate. In conclusion, the uterine sanitizer showed antimicrobial effects against endometritis-causing microorganisms. The dilution of antibiotics in the uterine sanitizer was stable and this association could potentiate the antimicrobial effects. Uterine sanitizer's safety and clinical efficacy in vivo remain to be tested.
Keywords: Alternative therapy; Antimicrobial resistance; Botukiller®; Equine; Infectious endometritis; Subfertility